Barriers to food quantity intake control and healthy eating among overweight and obese working Malay women in public service - Ismail, Suriani; Shamsuddin, Khadijah; Abdul Latif, Khalib; Abu Saad, Hazizi; Mohd Othman, Fadlan (Community Health Society Malaysia, 2015)
Introduction: The objective of this study is to look at the barriers faced by a group of working women who are overweight and obese that hinders control of their food quantity intake and healthy eating habit.